THE CONFIDENCE CODE : The Science and Art of Self-Assurance--What Women Should Know - Kay, Katty
Working women today are better educated and more well qualified than ever before. Yet men still predominate in the corporate world. In The Confidence Code, Claire Shipman and Katty Kay argue that the key reason is confidence. Combining cutting-edge re